The role of cognitive stimulation at home in low-income preschoolers' nutrition, physical activity and body mass index - Saskia Op den Bosch; Helena Duch (BMC, 2017)
Abstract Background Early childhood obesity disproportionately affects children of low socioeconomic status. Children attending Head Start are reported to have an obesity rate of 17.9%.This longitudinal study aimed to understand the relationship between cognitive stimulation at home and intake of junk food, physical activity and body size, for a nationally representative sample of 3- and 4-year old children entering Head Start. Methods We used The Family and Child Experiences Survey 2006. Cognitive stimulation at home was measured for 1905 children at preschool entry using items from the Home Observation Measurement of the Environment Short Form. Junk food consumption and physical activity were obtained from parent interviews at kindergarten entry. BMI z scores were based on CDC national standards. We analyzed the association between early cognitive stimulation and junk food consumption, physical activity and BMI, using multinomial and binary logistic regression on a weighted sample. Results Children who received moderate levels of cognitive stimulation at home had a 1.5 increase in the likelihood of consuming low amounts of junk food compared to children from low cognitive stimulation environments. Children who received moderate and high levels of cognitive stimulation were two and three times, respectively, more likely to be physically active than those in low cognitive stimulation homes. No direct relationship was identified between cognitive stimulation and BMI. Conclusion Prevention and treatment efforts to address early childhood obesity may consider strategies that support parents in providing cognitively stimulating home environments. Existing evidence-based programs can guide intervention in pediatric primary care.